2019
DOI: 10.21203/rs.2.19182/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A glucotolerant β-glucosidase from the fungus Talaromyces amestolkiae and its conversion into a glycosynthase for phenolic compounds glycosylation.

Abstract: Background: The interest for finding novel b-glucosidases that can improve the yields for the production of second-generation (2G) biofuels is still very high. One of the most desired features for these enzymes is the glucose tolerance, which allows them to act optimally under elevated glucose concentrations. Besides, there is an additional focus of attention on finding novel enzymatic alternatives for glycoside synthesis, for which a mutated version of glycosidases, named glycosynthases, have gained much inte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
2
0
0
Order By: Relevance
“…This is in good agreement with our previous results describing its production upon carbon exhaustion [9]. Besides, one GH1, previously characterized [25], and 4 GH3 β-glucosidases were also identified (Table 4). This profusion of -glucosidases could contribute to explain why this activity was so high in this medium, as compared with other conditions amestolkiae growing in raw glycerol confirmed the presence of BGL-3 and revealed that other interesting enzymes, including different β-glucosidases, can also be obtained for different biotechnological applications by exploiting the carbon starvation metabolism of T. amestolkiae.…”
Section: Fungal Secretome Analysissupporting
confidence: 91%
“…This is in good agreement with our previous results describing its production upon carbon exhaustion [9]. Besides, one GH1, previously characterized [25], and 4 GH3 β-glucosidases were also identified (Table 4). This profusion of -glucosidases could contribute to explain why this activity was so high in this medium, as compared with other conditions amestolkiae growing in raw glycerol confirmed the presence of BGL-3 and revealed that other interesting enzymes, including different β-glucosidases, can also be obtained for different biotechnological applications by exploiting the carbon starvation metabolism of T. amestolkiae.…”
Section: Fungal Secretome Analysissupporting
confidence: 91%
“…This is in good agreement with our previous results describing its production upon carbon exhaustion [9]. Besides, one GH1, previously characterized [25], and 4 GH3 βglucosidases were also identi ed (Table 4). This profusion of β-glucosidases could contribute to explain why this activity was so high in this medium, as compared with other conditions.…”
Section: Fungal Secretome Analysissupporting
confidence: 91%